2019
DOI: 10.3389/fnagi.2019.00352
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Maintenance of the Axis SIRT1-SIRT3 at Youth Level May Contribute to Brain Resilience in Middle-Aged Amateur Rugby Players

Abstract: Physical exercise performed regularly is known to improve health and to reduce the risk of age-related diseases. Furthermore, there is some evidence of cognitive improvement in physically active middle-aged and older adults. We hypothesized that long-term physically active middle-aged men may have developed brain resilience that can be detected with the analysis of peripheral blood markers. We aimed to analyze the activation of pathways potentially modulated by physical activity in a cohort of healthy amateur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…The A group is exposed to strenuous training, the objectives of the competition, and the eagerness to win or the fear of losing, and among other more subjective factors, we also find the ability to recover in the face of defeat, the sporting individuality, which is an important factor in victory, and the very renowned resilience [ 46 ]. Although these factors can positively affect their physical and psychological integrity, A do not always escape lockdown sequelae, as shown in different studies [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The A group is exposed to strenuous training, the objectives of the competition, and the eagerness to win or the fear of losing, and among other more subjective factors, we also find the ability to recover in the face of defeat, the sporting individuality, which is an important factor in victory, and the very renowned resilience [ 46 ]. Although these factors can positively affect their physical and psychological integrity, A do not always escape lockdown sequelae, as shown in different studies [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Life-long exercising elderly subjects have increased muscle SIRT3 and SOD levels [ 252 ] that counter age-associated oxidative stress and mitochondrial deterioration [ 253 ]. Elderly individuals who exercise have a youth-like gene expression profile (increased SIRT1, SIRT3, catalase, SOD1) and improved cognitive functions compared to age-matched sedentary controls [ 252 , 254 ]. Therefore, physical exercise deters the damaging effects of aging and protects against age-associated diseases [ 255 , 256 ].…”
Section: Sirt3 Regulates Interventions That Enhance Health and Lifespanmentioning
confidence: 99%
“…Neuroinflammation and peripheral inflammatory conditions associated with aging or some pathological conditions are known risk factors for triggering sporadic Alzheimer’s disease (AD) ( Bolós et al, 2017 ; Tejera et al, 2019 ). Furthermore, lower peripheral inflammation is one of the markers associated with preserved memory at middle age ( Corpas et al, 2019 ). Accordingly, experimental studies have shown neuroprotection by diverse anti-inflammatory agents against memory loss and AD-like pathology ( Corpas et al, 2017 ; Ettcheto et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%